Advanced materials for clean energy - Xu, Qiang (Materials scientist); Kobayashi, Tetsuhiko (CRC Press, 2015)
Research for clean energy is booming, driven by the rapid depletion of fossil fuels and growing environmental concerns as well as the increasing growth of mobile electronic devices. Consequently, various research fields have focused on the development of high-performance materials for alternative energy technologies. Advanced Materials for Clean Energy surveys the key developments in the science and engineering of the state-of-the-art materials for clean energy. The book provides a broad overview of materials for photovoltaics, solar energy conversion, thermoelectrics, piezoelectrics, supercapacitors, rechargeable batteries, fuel cells, and hydrogen production and storage. Each of these topics is covered by an experienced international group of contributors, all of whom are experts in their respective fields. The books gives you a valuable information for maximizing the efficiency of alternative energy approaches.